Aporphine alkaloids with in vitro antiplasmodial activity from the leaves of Phoebe tavoyana. Issue 1 (2nd January 2020) - Omar, Hanita; Fadaeinasab, Mehran; Taha, Hairin; Widyawaruyanti, Aty; Nafiah, Mohd Azlan; Rachmatiah, Tiah
Abstract: One new aporphine named tavoyanine A (1 ), along with four known aporphines laetanine (2 ), roemerine (3 ), laurolitsine (4 ), and boldine (5 ), and one morphinandienone type sebiferine (6 ) were isolated from the leaves of Phoebe tavoyana (Meissn.) Hook f. (Lauraceae). The isolation was achieved by chromatographic techniques, and the structural elucidation was performed via spectral methods. This paper also reports the antiplasmodial activity of roemerine (3 ), laurolitsine (4 ), boldine (5 ), and sebiferine (6 ). The results showed that 3 –6 have a potent inhibitory activity against the growth of Plasmodium falciparum 3D7 clone, with IC50 values of 0.89, 1.49, 1.65, and 2.76 µg/ml, respectively. Graphical Abstract: